2020
DOI: 10.1037/tra0000871
|View full text |Cite
|
Sign up to set email alerts
|

Rural–urban mental health disparities in the United States during COVID-19.

Abstract: The United States has more confirmed deaths from coronavirus 2019 than any other country in the world. State governors made decisions around social distancing in their jurisdictions, which caused schools and businesses to close. Those with broadband access continued a sense or normalcy in their lives. However, for the more than 20 million people who do not have broadband access, a different set of barriers has been experienced. These challenges are especially prominent in rural communities throughout various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 7 publications
3
74
0
1
Order By: Relevance
“…This could be attributed to better connectivity to regular updates and information regarding COVID-19, as well as close proximity to the hospital (Acuto 2020). On the other hand, the rural communities have poorer populations, poor access to COVID-19 information, and lesser hospital or medical facility as compared to urban area (Erwin et al 2020;Smith and Trevelyn 2019;Summers-Gabr 2020). These limitations could be the contributing factors to higher level of fear of COVID-19 among those aforementioned communities.…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributed to better connectivity to regular updates and information regarding COVID-19, as well as close proximity to the hospital (Acuto 2020). On the other hand, the rural communities have poorer populations, poor access to COVID-19 information, and lesser hospital or medical facility as compared to urban area (Erwin et al 2020;Smith and Trevelyn 2019;Summers-Gabr 2020). These limitations could be the contributing factors to higher level of fear of COVID-19 among those aforementioned communities.…”
Section: Discussionmentioning
confidence: 99%
“…For those experiencing IPV, the ability to have privacy away from the perpetrator for a telehealth visit may be a source for discord in the relationship and further violence. 57 …”
Section: Introductionmentioning
confidence: 99%
“…Rural-urban disparities in access to mental health services may also lead to state-level differences in mental health. 14 In addition, psychosocial characteristics may influence mental health symptoms. Previous work demonstrated that differences in adherence to public health measures and effective coping in response to public health crises by psychosocial characteristics lead to differences in mental health outcomes.…”
mentioning
confidence: 99%